Local envenoming by the coinsnake or Asian racer, Hemorrhois nummifer and mountain racer or leopard snake, Hemorrhois ravergieri (Serpentes: Colubridae, Colubrinae) in Iran: A reminder of the importance of species identification in the medical management of snakebites. (April 2023) - Kazemi, Seyed Mahdi; Jahan-Mahin, Mohammad Hossein; Mohammadian-Kalat, Tooba; Hosseinzadeh, Mahboubeh Sadat; Weinstein, Scott A.
Abstract: In Iran, there are approximately 4500–6500 snakebites per year, but fortunately only 3–9 of these are fatal. However, in some population centers such as Kashan city (Isfahan Province, central Iran), approximately 80% of snakebites are attributed to "non-venomous" snakes that are often comprised of several species of non-front-fanged snakes (NFFS). NFFS comprise a diverse group that constitute approximately 2900 species belonging to an estimated 15 families. We report here two cases of local envenoming from H. ravergieri, and one from H. nummifer that occurred in Iran. The clinical effects consisted of local erythema, mild pain, transient bleeding and edema. Two victims experienced progressive local edema that distressed the victims. The medical team's unfamiliarity with snakebites contributed to the incorrect clinical management of one victim including the contraindicated, ineffective provision of antivenom. These cases provide further documentation about local envenoming caused by these species, and also emphasize the need for regional medical personnel to receive increased training in order to improve familiarity with the local snake fauna and evidence-based snakebite management. Graphical abstract: Image 1 Highlights: Three cases of bites by two species of Asian racers, Hemmorhois ravergieri and H. nummifer are described. Three male victims bitten while handling captive or wild specimens. Local envenoming in the victims featured erythema, mild pain (persistent in one victim), local bleeding and progressive edema. Resolution required several days to almost two weeks. These cases reinforce the importance of accurate snake identification for effective medical management of snakebites.